Perancangan Sistem Informasi Penjualan Minuman Kemasan Berbasis Web Pada Toko Bambu Sejahtera Bekasi - Nandang Iriadi; Nia Rosdiana (Universitas Bina Sarana Informatika, 2017)
Toko Bambu Sejahtera is one of the companies selling drinks are located in areas Pondokgede – Bekasi. In the Toko Bambu Sejahtera authors sale systems analysis the current operation. That is done in the company sales are still not getting maximum revenue. Income that is not necessarily, the lack of promotion and lack of strategic place makes Toko Bambu Sejahtera yet known among the public at large. Therefore, the purpose of this study is to design an information system is a web-based product sales, or better known as E-Commerce using the programming language PHP and MySQL.Keywords : CV. Bambu Sejahtera, E-Commerce, Web, MySQL.